Modelling and experimental performance investigation of a transpired solar collector and underground heat exchanger assisted hybrid evaporative cooling system. (December 2021) - Abed, Fayadh M.; Zaidan, Maki H.; Hasanuzzaman, M.; Kumar, L.; Jasim, Abdullah K.
Abstract: Despite of being solar assisted, evaporative cooling devices in hot arid regions consume a substantial amount of electricity to produce sufficient cooling effect. This paper presents the design and performance analysis of a novel hybrid evaporative solar cooling system, aided by underground heat exchanger. A fan-assisted chamber composed of two vertical plenum space is intended to be cooling façade; the first plenum space is made up of black aluminum transpired plate and the second plenum space is shaped from the sand tile wall. The sand tile wall is used as an evaporative pad and sand wall with a perforated aluminum plate as a solar collector to evaporate the sprayed water. Simulation model of this system is built in MATLAB and it has been validated through experimental investigation carried in the hot and dry regions of Tikrit, Iraq. Experimental outcomes agree reasonably well with simulation results with only 2.3% incongruity. When the cooling system is powered only with transpired solar collector (TSC), indoor air temperature reduces 5 °C less and relative humidity 15% higher than ambient. In contrast, when TSC is assisted by underground heat exchanger, indoor air temperature falls 12 °C below and relative humidity 26% higher than ambient. Hence, using underground heat exchanger reduces cooling load by 50%. This passive evaporative cooling system is found to maintain room temperature between 2° to 6 °C below the ambient. This hybrid evaporative cooling system ensures enhanced comfort at lesser energy consumption. Highlights: Hybrid evaporative solar cooling with and without an underground heat exchanger. Comfort indoor air is 22–25 °C, while ambient air varies from 35 to 42 °C. Indoor temperature dropped 12 and 5 °C with and without underground heat exchanger. Reduction in cooling load up to 50% with an underground pipe.